Combining Part-Time Work and Social Benefits: Empirical Evidence from Finland - Salla Kalin; Tomi Kyyrä; Tuomas Matikka (Institute of Labor Economics (IZA), 2024)
We use detailed, population-wide data from Finland to provide evidence of the impact of earnings disregard policies on part-time work during unemployment spells, and describe the longer-run trends in combining part-time work and social benefits. We find that part-time work while receiving unemployment benefits is strongly concentrated in the service and social and health care sectors, and that women participate in part-time work much more commonly than men (25% vs. 12% of benefit recipients). The share of part-time workers among benefit recipients increased sharply from 10% to 18% over a few years after the implementation of earnings disregards in unemployment benefits and housing allowances, which allowed individuals to earn up to 300 euros per month without reductions in their benefits. Using variation in the impact of the reforms on incentives between individuals eligible for different types of benefits, we estimate a 16–28% increase in participation in part-time work due to the implementation of earnings disregards. However, we find no evidence of economically significant positive or negative effects of increased participation in part-time work on transitions to full-time employment.
Keywords: H24; J21; J22; 330; labor supply; social benefits; part-time work; earnings disregards